Development of total cost record for in-field transportation. A case study in Ladang Tanah Makmur Berhad / Nazrul Fazwan Mohd Zuki and Muhammad Aliuddin Bakar - Mohd Zuki, Nazrul Fazwan; Bakar, Muhammad Aliuddin (Faculty of Plantation and Agrotechnology, 2018)
In Malaysia, oil palm plantation is one of the major crop industries, and the usage of the tractor is one of the most important programmes of oil palm production. The total cost of the tractor can be measured based on the activity in-field operations. Nowadays, the problems of the high total cost of tractors in plantation can affect the financing problem towards the company. Tractor usage for in-field operation in the plantation is significant to make sure the Fresh Fruit Bunch deliver to the RAM within 24 hours. Besides, tractor usage also important to make sure the fertiliser bag reaches the working area on time. Movement of the tractor is based on the worker while during the broadcasting of fertilizer. The total cost of the tractor in Ladang Tanah Makmur Berhad was investigate. Data were collect from 2016 until 2017 on one tractor. The data were categorized into different costs constituting the cost of operating tractors such as repair and maintenance, fuel and lubricants, driver's wages, insurance, road taxes and miscellaneous costs. Different formula was used to analyze these operating costs. The results showed that the total cost in 2016 is higher than in 2017. Objectives of the study are to know the specific cost of the tractor annually. 1 take the total cost record of the tractor for the whole 2016 and 2017. Next, to evaluate and make recommendations on the ways that will enhance farm machinery utilisation and maintenance. The recommendation is essential for the company in order to reduce the cost and at the same time, achieve high yields. Third, study and analyse the operating cost of the tractor in the plantation. The last is to compare the tractor cost at the plantation with average.